Influence of various biofertilizers on root growth dynamics in sweet cherry (Prunus avium L.) cv. 'Vanda' - Sławomir Głuszek; Lidia Sas-Paszt; Edyta Derkowska; Beata Sumorok; Mirosław Sitarek (Horticultural Science, 2021)
The experiment was established in the Pomological Orchard of The National Institute of Horticultural Research in Skierniewice in a system of randomized blocks. The aim of the experiment was to investigate the impact of innovative organic fertilizers: BioIlsa, BioFeed Ecomix, biostimulator Ausma and mycorrhizal inoculum Mykoflor on the fine roots growth characteristics of 'Vanda' sweet cherry trees in comparison with NPK mineral fertilization. The experiment involved five combinations, in three repetitions of three trees each, treated with tested preparations. The study assessed the influence of fertilization on the lifespan of the roots, the depth of their formation, their diameter and survivorship using minirhizotron camera. The highest numbers of roots were found in the treatment where the plants were fertilized with NPK and the lowest following the use of the biofertilizer BioFeed Ecomix. The longest lifespan was shown by the roots of the trees treated with BioFeed Ecomix - 347 days, and the shortest - by those fertilized with the Ausma - 225 days. The lifespan of the roots increased with their diameter. The roots that lived the longest had a diameter in the range from 0.9 to 1.0 mm - 568 days, and the shortest-living were the roots with a diameter smaller than 0.3 mm - 238 days. The roots that formed in late autumn and winter had the shortest median lifespan of 159 days, while the roots formed in the spring where characterized by the longest lifespan of 300 days. The lifespan of the roots formed close to the soil surface was the shortest - 225 days, while that of the roots formed at a depth of 10 to 20 cm was the longest - 326 days. Biological origin, organic nitrogen rich fertilizers positively influence on fine roots lifespan and longevity. Mineral fertilization increases number of new formed roots.